Genesis of Scientific Approaches to the Theory of Human Capital - Demchenko Oleksandr V. (Bìznes Inform)
The article is devoted to the disclosure of the main trends in scientific views on the category of «human capital» and the development of the theoretical foundations of the study of human capital. The study of the genesis of scientific approaches to the theory of human capital is critical for understanding its evolution and determining the directions for further development. A chronogram of the historical stages of evolution of the theory of «human capital» within the framework of the leading schools of economic theory has been built. It is defined that the complexity of the connection between a person and the performed labor is caused by its subject-objectivity: a person is a subject of the labor process, independently determining what to do, from what to do and for what to do; at the same time, a person is an object of the labor process, since the main task of social production is to satisfy human needs. It is this complexity that causes numerous contradictions that naturally arise in the production process. They in turn are the reason for the ongoing debate about the essence of human capital, its purpose and the factors that form it. It is substantiated that the main factor in the formation of human capital is investment in the carrier of human capital – a human person. The importance of investment in human capital is so great that it exceeds investment in fixed capital. It is generalized that the fundamental basis of the process of social production, without which this process is impossible in principle, is human labor. The theoretical substantiation of the category of «human capital» has come a long historical way of development. Scientific and technological progress and humanization of social relations have become the main factors in the transformation of the factor of production «labor force» into the factor of production «human capital». It is summarized that human capital is a reserve of health, knowledge, skills, abilities, motivations, determined by scientific and technological progress and humanization of social relations, formed as a result of investments, which provides income to their bearer, contributes to the growth of labor productivity and well-being of society.